Swimming Marine Synechococcus Strains with Widely Different Photosynthetic Pigment Ratios Form a Monophyletic Group - Toledo, Gerardo (American Society for Microbiology, 1999)
Unicellular marine cyanobacteria are ubiquitous in both coastal and oligotrophic regimes. The contribution of these organisms to primary production and nutrient cycling is substantial on a global scale. Natural populations of marine Synechococcus strains include multiple genetic lineages, but the link, if any, between unique phenotypic traits and specific genetic groups is still not understood. We studied the genetic diversity (as determined by the DNA-dependent RNA polymerase rpoC1 gene sequence) of a set of marine Synechococcus isolates that are able to swim. Our results show that these isolates form a monophyletic group. This finding represents the first example of correspondence between a physiological trait and a phylogenetic group in marine Synechococcus. In contrast, the phycourobilin (PUB)/phycoerythrobilin (PEB) pigment ratios of members of the motile clade varied considerably. An isolate obtained from the California Current (strain CC9703) displayed a pigment signature identical to that of nonmotile strain WH7803, which is considered a model for low-PUB/PEB-ratio strains, whereas several motile strains had higher PUB/PEB ratios than strain WH8103, which is considered a model for high-PUB/PEB-ratio strains. These findings indicate that the PUB/PEB pigment ratio is not a useful characteristic for defining phylogenetic groups of marine Synechococcus strains.